Data‐driven modelling of joint debris flow release susceptibility and connectivity. Issue 11 (15th June 2022) - Steger, Stefan; Scorpio, Vittoria; Comiti, Francesco; Cavalli, Marco
Abstract: In mountain basins, sediment supply to the fluvial system occurs mainly through episodic geomorphic processes—such as debris flows and other landslide types—whose effectiveness is strongly influenced by the structural connectivity within a catchment. This paper presents a novel data‐driven approach to identify and map areas that are simultaneously susceptible to debris flow initiation and structurally connected to the main channel network (i.e. relevant sediment source areas for predicting and mitigating flood hazards in the river channels). The presented approach comprises: (i) the visual interpretation, delineation, mapping and classification of event‐specific connected and disconnected debris flow areas in three catchments of the Italian Alps; (ii) the development of data‐driven debris flow release susceptibility models that are combined with quantitatively classified index of connectivity (IC) maps; and (iii) a thorough evaluation of the approach, including an assessment of its spatial transferability across the catchments. The main results show: (i) quantitative IC thresholds to discriminate connected from disconnected debris flow release areas; (ii) statistically well‐performing and geomorphically plausible debris flow release susceptibility models for the three basins; (iii) diverse joint debris flow connectivity–susceptibility maps that allow identifying zones which are differently relevant in terms of debris flow connectivity. This work also highlights the spatial transferability of the approach, associated benefits and potential drawbacks, as well as the utmost importance of a thorough combined quantitative and qualitative (i.e. geomorphic plausibility) evaluation of the underlying results. The proposed approach is rather simple and requires few basic input data, and can therefore be applied over vast areas (e.g. to support regional‐scale hazard assessments or sediment management plans). Abstract : Summary of the methodological framework used in this study to map areas that are susceptible to debris flow initiation and structually connected to the main channel network.